Registration-Based Morphing of Active Contours for Segmentation of CT Scans - Yuan-Nan Young; Doron Levy (Mathematical Biosciences and Engineering)
We present a new algorithm for segmenting organs in CT scans forradiotherapy treatment planning.Given a contour of an organ that is segmentedin one image, our algorithm proceeds tosegment contours that identify the same organ inthe consecutive images.Our technique combines partial differential equations-based morphing activecontours with algorithms for joint segmentation and registration. Thecoupling between these different techniquesis done in order to deal with the complexityof segmenting ''real'' images, where boundariesare not always well defined, and the initialcontour is not an isophote of the image.